Galectin-1 expression in the serum and placenta of pregnant women with fetal growth restriction and its significance - Xiao-Xiao Jin; Xiang Ying; Min-Yue Dong (BMC, 2021)
Abstract Background This study aims to investigate galectin-1 (Gal-1) expression in the serum and placenta of pregnant women with fetal growth restriction (FGR) and its significance. Methods Thirty-one pregnant women with single-birth FGR but without comorbidities, eight pregnant women with FGR and preeclampsia (PE), and eight pregnant women with FGR and gestational diabetes mellitus (GDM) were enrolled as the study group, while 20 pregnant women with normal singleton pregnancy in the same period were enrolled as the control group. The serum Gal-1 level was detected using an enzyme-linked immunosorbent assay (ELISA), and Gal-1 expression in the placenta was detected by western blot. Results The results revealed that, compared with the control group, the serum Gal-1 level decreased in the women with FGR without comorbidities, and the difference was statistically significant (P < 0.001). Compared with the control group, the difference in serum Gal-1 expression in the FGR-PE group was not statistically significant (P = 0.29). The peripheral serum Gal-1 level decreased in the FGR-GDM group compared with the control group, and the difference was statistically significant (P < 0.001). The serum Gal-1 level was positively correlated with birth weight (r2 = 0.172, P < 0.01). Compared with the control group, the Gal-1 expression level decreased in the placenta of the pregnant women with FGR without comorbidities (P < 0.05). Conclusions Gal-1 exhibits low expression in the serum and placenta of pregnant women with FGR. In addition, Gal-1 may be involved in the pathogenesis of FGR and could represent a new diagnostic marker of the disease.